Longer Breastfeeding Associated with Childhood Anemia in Rural South-Eastern Nigeria - Sean Buck; Kevin Rolnick; Amanda A. Nwaba; Jens Eickhoff; Kelechi Mezu-Nnabue; Emma Esenwah; Olachi J. Mezu-Ndubuisi (International Journal of Pediatrics)
Introduction. Child mortality rate in sub-Saharan Africa is 29 times higher than that in industrialized countries. Anemia is one of the preventable causes of child morbidity. During a humanitarian medical mission in rural South-Eastern Nigeria, the prevalence and risk factors of anemia were determined in the region in order to identify strategies for reduction. Methods. A cross-sectional study was done on 96 children aged 1-7 years from 50 randomly selected families. A study questionnaire was used to collect information regarding socioeconomic status, family health practices, and nutrition. Anemia was diagnosed clinically or by point of care testing of hemoglobin (Hb) levels. Results. 96 children were selected for the study; 90 completed surveys were analyzed (43% male and 57% females). Anemia was the most prevalent clinical morbidity (69%), followed by intestinal worm infection (53%) and malnutrition (29%). Mean age (months) at which breastfeeding was stopped was 11.8 (±2.2) in children with Hb <11mg/dl (severe anemia), 10.5±2.8 in those with Hb = 11-11.9mg/dl (mild-moderate anemia), and 9.4±3.9 in children with Hb >12mg/dl (no anemia) (P=0.0445). Conclusions. The longer the infant was breastfed, the worse the severity of childhood anemia was. Childhood anemia was likely influenced by the low iron content of breast milk in addition to maternal anemia and poor nutrition. A family-centered preventive intervention for both maternal and infant nutrition may be more effective in reducing childhood anemia and child mortality rate in the community.